Maternal nutritional awareness and iron deficiency anemia in children aged 6 months–2 years in a tertiary care hospital in Coimbatore, Tamil Nadu - Sheik, Shahana Parvin; Saidalikutty, Fouzeamol (Indian Journal of Child Health, 2022)
Objective: This study aims to analyze the risk factors and vital role of mothers in prevention of nutritional anemia in the early childhood. Methods: A hospital-based cross-sectional study done in Coimbatore for 2 years. Using a pre-tested structured validated tool, mothers of children aged 6 months–2 years were interviewed to collect information on factors contributing to anemia with special regard to maternal knowledge. Results: Anemia was more in the latter half of infancy (67.2%) with male predominance (60.5%). An affirmative association between increased cow’s milk intake and low hemoglobin was present (p=0.002). Employed and less educated mothers had more anemic children (p<0.05). Of 16% mothers classified as “poor” awareness, 95.45% children had low hemoglobin (p<0.05). Conclusion: Recognizing the causative factors plays an essential role in preventing iron deficiency anemia (IDA). Exclusive breastfeeding must be promoted, along with avoiding excessive cow’s milk intake. Intervening at the right period with age-appropriate foods becomes a necessity. Maternal illiteracy has a positive correlation with anemia in infants. Improving maternal awareness by the physicians will pave the road toward a nation free from anemia.